Tribological performance and corrosion behavior of CoCrMo alloy - Hadda Rezzag; Latifa Kahloul; Hacène Chadli; Alima Mebrek; Adel Saoudi (Fracture and Structural Integrity)
The present work focuses on the Tribological properties and corrosion behavior evaluation of sintered CoCrMo alloy. The CoCrMo alloy was elaborated by Powder metallurgy process at various sintering temperatures (1200°C, 1250°C and 1300°C). The structural properties were characterized by X-ray diffraction and scanning electron microscopy. The tribological characteristics were measured using a dry disc-ball tribometer. The corrosion behavior of the samples was studied using different electrochemical tests in a simulated physiological environment (Hank’s solution). The obtained results show that higher sintering temperatures have a positive impact on the tribological behavior as well as the corrosion resistance of CoCrMo alloys. The sintered samples at 1300°C showed a better resistance to friction wear and a lower corrosion rate.